2021
DOI: 10.3390/su13126896
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of Mode Choice Decision for Utilitarian and Hedonic Trips: Evidence from Iran

Abstract: A sizeable body of literature reveals a strong relationship between mode choice and health status. Therefore, society would benefit from travel if transportation and urban planners motivated more individuals to satisfy their desire for travel by active transportation rather than motorized transportation. Despite rich existing literature about the relations between the built environment and travel, we still need to address some research gaps in explaining travel mode choice. As a shortcoming, identifying and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 82 publications
(133 reference statements)
0
7
0
Order By: Relevance
“…Despite the significant empirical support for the Theory of Planned Behaviour, Theory of Interpersonal Behaviour, and Norm Activation Model in the prediction of transportation mode choice, these models have primarily been tested in the context of utilitarian trips (Hoffmann et al, 2017;Mirzaei & Mignot, 2021). Namely, utilitarian trips comprise of routine and need-based trips (i.e., commuting to work or school, running errands, or seeking medical care), while hedonic trips, in contrast, focus on engaging in leisure activities (i.e., tourism, events, or recreational activities) (Mirzaei & Mignot, 2021). A notable difference is that in utilitarian trips, travel is often viewed as a disutility or a means to an end; whereas travel for hedonic trips is often valued and viewed as part of the overall leisure experience (Mirzaei & Mignot, 2021).…”
Section: Psychological Determinants Of Travel Mode Choice Across Trip...mentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the significant empirical support for the Theory of Planned Behaviour, Theory of Interpersonal Behaviour, and Norm Activation Model in the prediction of transportation mode choice, these models have primarily been tested in the context of utilitarian trips (Hoffmann et al, 2017;Mirzaei & Mignot, 2021). Namely, utilitarian trips comprise of routine and need-based trips (i.e., commuting to work or school, running errands, or seeking medical care), while hedonic trips, in contrast, focus on engaging in leisure activities (i.e., tourism, events, or recreational activities) (Mirzaei & Mignot, 2021). A notable difference is that in utilitarian trips, travel is often viewed as a disutility or a means to an end; whereas travel for hedonic trips is often valued and viewed as part of the overall leisure experience (Mirzaei & Mignot, 2021).…”
Section: Psychological Determinants Of Travel Mode Choice Across Trip...mentioning
confidence: 99%
“…Namely, utilitarian trips comprise of routine and need-based trips (i.e., commuting to work or school, running errands, or seeking medical care), while hedonic trips, in contrast, focus on engaging in leisure activities (i.e., tourism, events, or recreational activities) (Mirzaei & Mignot, 2021). A notable difference is that in utilitarian trips, travel is often viewed as a disutility or a means to an end; whereas travel for hedonic trips is often valued and viewed as part of the overall leisure experience (Mirzaei & Mignot, 2021). As a result, studies in utilitarian contexts often lack both sufficient application and generalizability to hedonic trips, such as the attendee travel to special events.…”
Section: Psychological Determinants Of Travel Mode Choice Across Trip...mentioning
confidence: 99%
See 2 more Smart Citations
“…In order to develop strategies that promote greater adherence to the use of bicycles for transportation in large cities, it is crucial to identify the antecedents and the consequences of this choice (Gerike et al, 2019;Handy et al, 2014). After all, since different factors determine the choice of the means of transportation in urban areas, specific policies must be designed to encourage the use of bicycles in each case and situation (Mirzaei & Mignot, 2021). An extensive exploratory study conducted in Switzerland found three main motivations behind the use of bicycles as a vehicle for commuting to work: the wellbeing (hedonic), independence (utilitarian) and civic engagement (social and ecological) of users.…”
Section: Introductionmentioning
confidence: 99%